A RETROSPECTIVE ANALYSIS OF CARDIOTOXICITY WITH DOXORUBICIN AND TRASTUZUMAB IN BREAST CANCER HER-2 POSITIVE PATIENTS - Yemineni Gopi,; Yasam Shree,; Dasari Rahul Pramodh Kumar,; Kommineni Sai Teja,; Bodempudi Naga Venkata Sai,; T.V.Siva Ramakrishna,; K.S. Abhishek Raghava,; Rama Rao Nadendla, (The Bioscan, 2025)
Background: Breast cancer is the most prevalent cause of mortality for women worldwide, and its prevalence is rising in emerging countries. The widespread availability of numerous drugs that target the HER2 receptor has led to improvements in survival rates for patients with Human Epidermal Growth Factor Receptor-2-positive (HER2+) breast cancer over the past few decades. Aim: To study the cardiotoxicity associated with the use of doxorubicin and trastuzumab in HER-2 positive breast cancer patients, a retrospective analysis. Methodology: A retrospective analysis, Patients were screened based on inclusion and exclusion criteria. The self-designed and validated questionnaire was used to assess the cardiotoxicity with doxorubicin and trastuzumab in breast cancer HER-2 positive patients. Collected data was tabulated and interpreted using statistical software. Results: Upon reviewing demographic data from 117 subjects, it was noted that breast cancer is most prevalent among individuals over 65 years old, with 51 (40.51%) subjects, significant at p=0.03436. All subjects in the study were female except one male. A higher proportion of subjects with a BMI of 30-34 kg/m2 were reported, with 53 (45.20%) subjects, significant at p=0.04131. Among social habits, regular smokers were found to be at a higher risk of breast cancer, significant at p=0.02115. Late menopause was associated with increased risk, with 54 (48%) subjects, significant at p=0.03887. The assessment of cardiotoxicity with doxorubicin pre- and post-therapy using ejection fraction (EF) was statistically analyzed with a p-value of 0.000017. Trastuzumab at a dose of 2mg/kg showed an EF assessment of 0.2035, statistically insignificant for cardiotoxicity. However, at a dose of 8mg/kg, trastuzumab showed a statistically significant EF assessment of 0.000018. Conclusion: This study found that breast cancer is common among older individuals, those with higher BMI, lower socioeconomic status, service workers, late menopause, and regular tobacco users. Trastuzumab at 2mg/kg showed no cardiotoxicity, while both trastuzumab at 8mg/kg and doxorubicin exhibited similar cardiotoxicity effects, with more deaths associated with doxorubicin. Therefore, trastuzumab at a lower dose appears to be effective and safe.